Analisa dan Perancangan Human Resource Information System di Bandara Soekarno – Hatta - Ratna Kusumawardani (Asosiasi Pendidikan Tinggi Informatika dan Komputer Provinsi DKI Jakarta, 2022)
This study discusses the Human Resources Information System (HRIS). The problem that occurs in the study is that natural resource management is still done manually using Microsoft Excel so that in the data management process it is still not neat and there is a high possibility of data loss. The use of the Human Resources Information System can minimize and assist HR in managing and storing data with thousands of HR data into the database. The method used in this research is the PIECES method (Performance, Information, Economy, Control, Efficiency and Service). This method was chosen because it is able to obtain more specific issues. The result of the research is a Human Resources Information System which was built using the PHP programming language with a MySQL database. The application that was built aims to manage, store and maintain human resource data from various work units so that it will be more effective and efficient.